Improving management of psoriasis patients receiving biological treatment: A qualitative approach. Issue 3 (1st January 2021) - Trettin, Bettina; Feldman, Steven; Andersen, Flemming; Danbjørg, Dorthe B.; Agerskov, Hanne
Abstract: Aim: To investigate psoriasis patients' and healthcare professionals' experiences and perspectives of follow‐up consultations. Design: A qualitative study with a phenomenological‐hermeneutic approach. Method: Participant observations of consultations and semi‐structured interviews were conducted with patients receiving biological treatment, together with two focus groups with healthcare professionals, from June 2018–January 2019. Data were analysed using a qualitative structured approach based on Paul Ricoeur's philosophy of interpretation. Results: Consultations had a strong biomedical and corrective approach focusing on lifestyle behaviour change, measurements and permanent routines. Healthcare professionals felt the need for enhanced competencies providing lifestyle behaviour change support and the possibility of providing patients more specific strategies. They were faced with a dilemma between lacking the right skills and having a professional duty. The frequent follow‐up visits did not fit in with the patients' everyday lives.